CUMYL-4CN-BINACA Is an Efficacious and Potent Pro-Convulsant Synthetic Cannabinoid Receptor Agonist - Kevin, Richard C.; Anderson, Lyndsey; McGregor, Iain S.; Boyd, Rochelle; Manning, Jamie J.; Glass, Michelle; Connor, Mark; Banister, Samuel D. (Frontiers in Pharmacology, 2019)
Synthetic cannabinoid receptor agonists (SCRAs) are the largest class of new psychoactive substances (NPS). New examples are detected constantly, and some are associated with a series of adverse effects, including seizures. CUMYL-4CN-BINACA (1-(4-cyanobutyl)-N-(2-phenylpropan-2-yl)indazole-3-carboxamide) is structurally related to potent, cumylamine-derived SCRAs such as 5F-CUMYL-PINACA, but is unusual due to a terminal aliphatic nitrile group not frequently encountered in SCRAs or pharmaceuticals. We report here that CUMYL-4CN-BINACA is a potent CB1 receptor agonist (Ki = 2.6 nM; EC50 = 0.58 nM) that produces pro-convulsant effects in mice at a lower dose than reported for any SCRA to date (0.3 mg/kg, i.p). Hypothermic and pro-convulsant effects in mice could be reduced or blocked, respectively, by pretreatment with CB1 receptor antagonist SR141716, pointing to at least partial involvement of CB1 receptors in vivo. Pretreatment with CB2 receptor antagonist AM-630 had no effect on pro-convulsant activity. The pro-convulsant properties and potency of CUMYL-4CN-BINACA may underpin the toxicity associated with this compound in humans.